Biết (F( x ) = - dfrac(1)(((x^2)))) là một nguyên hàm của hàm số (y = dfrac((f( x )))(x).) Tính (int (f'( x )ln xdx.) )

Lưu lại

Biết $F\left( x \right) =  - \dfrac{1}{{{x^2}}}$ là một nguyên hàm của hàm số $y = \dfrac{{f\left( x \right)}}{x}.$ Tính $\int {f'\left( x \right)\ln xdx.} $ 

Đáp án: B

Đặt $\left\{ \begin{array}{l}\ln x = u\\f'\left( x \right)dx = dv\end{array} \right. \Leftrightarrow \left\{ \begin{array}{l}\dfrac{1}{x}dx = du\\v = f\left( x \right)\end{array} \right.$

Ta có $\int {f'\left( x \right)\ln xdx}  = \ln x.f\left( x \right) - \int {\dfrac{1}{x}f\left( x \right)dx}  = \ln x.f\left( x \right) + \dfrac{1}{{{x^2}}} + C$

(vì theo giả thiết $\int {\dfrac{{f\left( x \right)}}{x}dx}  =  - \dfrac{1}{{{x^2}}} + C$)

Lại có ${\left( {F\left( x \right)} \right)^\prime } = \dfrac{{f\left( x \right)}}{x} \Leftrightarrow \dfrac{{f\left( x \right)}}{x} = {\left( { - \dfrac{1}{{{x^2}}}} \right)^\prime } \Leftrightarrow \dfrac{{f\left( x \right)}}{x} = \dfrac{2}{{{x^3}}} \Rightarrow f\left( x \right) = \dfrac{2}{{{x^2}}}$

Suy ra $\int {f'\left( x \right)\ln xdx}  = \ln x.f\left( x \right) + \dfrac{1}{{{x^2}}} + C = \dfrac{{2\ln x}}{{{x^2}}} + \dfrac{1}{{{x^2}}} + C.$

Chọn B

TOP THÀNH VIÊN NỔI BẬT

    Xem top 100 thành viên